Politeness Principles Of Flouting Maxims Used By The Characters Of “The School Of Rock” Movie - Steffanie Amalia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The primary objective of this research is to examine and analyze the several instances in which the characters in the movie entitled